พระพุทธศาสนาเถรวาทกับสุนทรียศาสตร์ - ไทยมิตร, นายแสงอาทิตย์ (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 1 No 1 (2018): ปีที่ 1 ฉบับที่ 1 ประจำเดือนมกราคม - มิถุนายน 2561, 2018)
The objective of this article is to study the doctrines of Buddhism on aesthetics. The result found that the Buddhist aesthetics is classified into two kinds – one is that adheres to the world and the other kind is transcendent aesthetics or Dhamma aesthetics. The secular Buddhist aesthetics means the teachings of arts and beauty which can be seen and understood by the world and this kind of aesthetics still clings to defilements in human’s mind. The transcendent Buddhist aesthetics means the doctrines of beauty resulting from seeing the nature of truth as they are. The man with Dhamma in mind conducts his behavior peacefully and truly. The other people respect him as Dhamma man or holy person with a beautiful mind. The one who sees the nature of truth can know and realize the transcendent Buddhist aesthetics as the same. Apart from conducting good behavior, he also spreads the stream of Dhamma beauty surrounding the people around him Keywords: Theravada Buddhism, Aesthetics